Preventive behaviours towards influenza A(H1N1)pdm09 and factors associated with the intention to take influenza A(H1N1)pdm09 vaccination - Cho Naing; Rachel Yi Ping Tan; Wai Cheong Soon; Jehangirshaw Parakh; Sandip Singh Sanggi (Elsevier, 2012)
Summary: Purpose: (i) To determine knowledge of, and self-protecting preventive behaviours towards influenza A(H1N1)pdm09 and (ii) to identify the factors influencing intention to take influenza A(H1N1)pdm09 vaccination among the study population. Materials and methods: This is a cross-sectional survey carried out in Mantin Town, a semi-urban area of Malaysia. A structured questionnaire consisted of sociodemographic characteristics, knowledge of pandemic influenza symptoms, mode of transmission, self-protecting preventive behaviours, and intention to receive the influenza A(H1N1)pdm09 vaccine was used for face-to-face interviews with the household members. Results: Of 230 who heard about pandemic influenza A(H1N1), 86% had misconception about mode of transmission of influenza A(H1N1)pdm09, and 52% had sufficient self-protecting behaviours. A majority (58.3%; 134/230) had intended to receive the vaccine. In the multivariate analysis, the intention to get vaccinated was significantly higher among 'those who trusted in efficacy of vaccine for prevention of influenza A(H1N1)pdm09' (p < 0.001), 'those who were equipped with higher education level' (p = 0.015) and 'those who worry about themselves contracting illness' (p = 0.008). Conclusions: Our findings highlight the need to scale up the community's knowledge regarding influenza A(H1N1)pdm09. Recognizing the factors affecting the acceptance of vaccination documented in this study will allow decision makers to devise effective and efficient vaccination strategies. Keywords: Influenza A(H1N1)pdm09, Knowledge, Self-protection, Behaviours, Vaccination